Durvalumab with or without tremelimumab combined with particle therapy for advanced hepatocellular carcinoma with macrovascular invasion: protocol for the DEPARTURE phase Ib trial. Issue 4 (8th April 2022) - Ogasawara, Sadahisa; Koroki, Keisuke; Makishima, Hirokazu; Wakatsuki, Masaru; Takahashi, Asahi; Yumita, Sae; Nakagawa, Miyuki; Ishino, Takamasa; Ogawa, Keita; Fujiwara, Kisako; Iwanaga, Terunao; Sakuma, Takafumi; et al.
Abstract : Introduction: Advanced hepatocellular carcinoma (HCC) with macrovascular invasion (MVI) has the worst prognosis among all phenotypes. This trial aims to evaluate whether treatment with durvalumab, alone or in combination with tremelimumab, plus particle therapy is a safe and synergistically effective treatment in patients with advanced HCC and MVI. Methods and analysis: This phase Ib, multicentre (two sites in Japan), open-label, single-arm, investigator-initiated clinical trial will assess durvalumab monotherapy in combination with particle therapy (cohort A) and that of durvalumab plus tremelimumab in combination with particle therapy (cohort B) for patients with advanced HCC with MVI. Cohort A will receive 1500 mg durvalumab every 4 weeks. Cohort B will receive 1500 mg durvalumab every 4 weeks in principle and 300 mg tremelimumab only on day 1 of the first cycle. Carbon-ion radiotherapy will be administered after day 8 of the first cycle. The primary endpoints are rates of any and severe adverse events, including dose-limiting toxicities (DLTs); secondary endpoints are overall survival, 6-month survival, objective response, 6-month progression-free survival and time to progression. Patients are initially enrolled into cohort A. If cohort A treatment is confirmed to be tolerated (ie, no DLT in three patients or one DLT in six patients), the trial proceeds to enrol more patients into cohort B. Similarly, if cohort B treatment is confirmed to be tolerated (ie, no DLT in three patients or one DLT in six patients), a total of 15 patients will be enrolled into cohort B. Ethics and dissemination: This study was approved by the ethics committees of the two participating institutions (Chiba University Hospital and National Institutes for Quantum (approval number: 2020040) and Radiological Science and Technology, QST Hospital (approval number: C20-001)). Participants will be required to provide written informed consent. Trial results will be reported in a peer-reviewed journal publication. Trial registration number: jRCT2031210046.